FORMULATION DEVELOPMENT AND EVALUATION OF TAMOXIFEN CITRATE LIQUISOLID SYSTEM - DNYANESH WALUNJ; YOGESH SHARMA; SWATI RAWAT; KIRAN BHISE (International Journal of Pharma and Bio Sciences, 2012)
The in vitro dissolution property of poorly water soluble Tamoxifen citrate was improved by exploring the potential of Liquisolid system (LS). Different LS compacts were prepared using a mathematical model to calculate the required quantities of powder and liquid ingredients to produce acceptably flowable and compressible admixture. Avicel PH 102, Aerosil 200, Cross Carmellose Sodium and Propylene glycol were employed as carrier, coating material disintegrant and non volatile solvent respectively for preparing liquisolid compacts. The IR, DSC and XRD studies confirmed that there was no significant interaction between the drug and excipients used in LS compacts. The drug release rates of LS compacts were distinctly higher as compared to directly compressed tablets, which show significant benefit of LS in increasing wetting properties and surface area of drug available for dissolution. From this study it was concluded that the liquisolid technique is a promising alternative for improvement of dissolution property of water-insoluble drugs.